Advancing engineering design problem-exploring practice: interviews with industry professionals - Obieke, Chijioke C.; Milisavljevic-Syed, Jelena; Han, Ji (Taylor & Francis, 2025)
Studies highlight that conceptualising and identifying a new engineering design problem (EDP) is vital, as the solution can benefit society. However, this essential activity, referred to as engineering design problem-exploring (EDPE), is lacking in practice in engineering design. Design engineers appear to focus on providing an engineering design solution (EDS) while their role in EDPE is rarely practised. A new EDP drives innovations and inventions, and there is a need to encourage, advance and sustain the practice of identifying new EDPs. The aim of this study is to empirically highlight the underlying determinants of the scarce practice of EDPE and suggest how to advance and sustain the practice. Interviews were conducted with 32 professionals within the engineering design community, comprising 28 practitioners and four specialists – a lecturer, an inventor, and two expert trainers in creativity and problem-solving. The results of the analyses informed the suggested approaches in this study to advance and sustain the EDPE practice.
Keywords: Design Practice & Management; 3303 Design; 4005 Civil engineering; Problem-exploring; engineering design; conceptual design; creativity; concept generation